Digital circuit system using VHDL - Gupta, Shipra (S.K.Kataria & Sons, 2012)
Table of Contents Introduction to VHDL VHDL Statements Combinational Circuit Design Sequential Circuit Design Design of Micro Computer Design with CPLD's and FPGA's Additional Topics VHDL Program for Lab Question Bank Model Question Papers Index.